Challenges in Controlling Proliferation of Small Arms in Nepal - Bogati, Subindra (Journal of APF Command and Staff College, 2018)
The paper aims to study and present the status of proliferation of small arms in Nepal. Nepal has been facing the problems of illicit weapons and this needs proper response from the government so that long-lasting solution can be probed. There is risk of misusing those weapons against anyone. A program to destroy the illegal arms should immediately be launched.